Multidrug-resistant tuberculosis - Lemos,Antônio Carlos Moreira (2013)
Despite the efforts made worldwide to reduce the number of cases of drug-susceptible tuberculosis, multidrug-resistant tuberculosis (MDR-TB) constitutes an important public health issue. Around 440,000 new cases of MDR-TB are estimated annually, although in 2008 only 7% of these (29,423 cases) were notified. The laboratory tests for diagnosing resistance may be phenotypic (based on culture growth in the presence of drugs) or genotypic (i.e. identification of the presence of mutations that confer resistance). The urgent need for a rapid means of detecting resistance to anti-TB drugs has resulted in the development of many genotypic methods over recent years. The treatment of MDR-TB is expensive, complex, prolonged (18-24 months) and associated with a higher incidence of adverse reactions. Some basic principles must be observed when prescribing an adequate treatment regimen for MDR-TB: (a) the association of at least four drugs (three of which should not have been used previously); (b) use of a fluoroquinolone; and (c) use of an injectable anti-TB drug. In Brazil, the therapeutic regimen for MDR-TB has been standardized and consists of five drugs: terizidone, levofloxacin, pyrazinamide, ethambutol and an aminoglycoside (streptomycin or amikacin). Pulmonary resection is an important tool in the coadjuvant treatment of MDR-TB. While a recent meta-analysis revealed an average cure rate of MDR-TB of 69%, clinical studies are currently being conducted with new drugs and with drugs already available on the market but with a new indication for TB, with encouraging results that will enable more effective treatment regimens to be planned in the future.